Guardería infantil en Trebujena - RGR (1999)
Cadiz, España 1999. Concurso primer premio, por Rubiño-García Márquez-Rubiño
Keywords: ESPAÑA; GARCÍA MÁRQUEZ, PURA; RUBIÑO, IGNACIO; RUBIÑO, LUIS; GUARDERIAS INFANTILES; CONCURSOS